2004
DOI: 10.1001/archotol.130.8.943
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Proteolytic Enzymes in Head and Neck Cancer–Associated Fibroblasts

Abstract: To elucidate tumor-stromal interactions during tumor invasion by assessing the expression of proteolytic enzymes by carcinoma-associated fibroblasts (CAFs) in vivo using complementary DNA (cDNA) array analysis. Methods: Tumor-associated stroma was isolated from tumor and adjacent mucosal specimens of the same patient by laser capture microdissection, and the messenger RNA (mRNA) was assessed by cDNA microarray specific for proteolytic enzymes and their inhibitors. Protein overexpression was then analyzed by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 19 publications
0
38
0
1
Order By: Relevance
“…These enzymes are capable of cleaving most ECM components, as well as other biologically important proteins such as growth factors, other proteases, adhesion molecules, and cell surface receptors (Table 1). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] With a widening understanding of MMP substrates, a more complex role for these enzymes in tumor growth and metastasis has been appreciated.…”
Section: Matrix Metalloproteasesmentioning
confidence: 99%
See 3 more Smart Citations
“…These enzymes are capable of cleaving most ECM components, as well as other biologically important proteins such as growth factors, other proteases, adhesion molecules, and cell surface receptors (Table 1). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] With a widening understanding of MMP substrates, a more complex role for these enzymes in tumor growth and metastasis has been appreciated.…”
Section: Matrix Metalloproteasesmentioning
confidence: 99%
“…However, most peritumoral MMPs are synthesized by host cells such as endothelial cells, fibroblasts, and inflammatory cells rather than tumor cells themselves. 24,30 In fact, elegant mouse models of tumor progression in mice have demonstrated that MMP-9 expression by bone marrow-derived cells contributes to an aggressive phenotype in squa-mous cell carcinoma. 21,31 Last, MMPs have both tumor promoting and inhibitory effects.…”
Section: Matrix Metalloproteases In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Membrane-type I matrix metalloproteinase (MT1-MMP) is a potent collagenase highly expressed in human and mouse breast carcinomas, where it has been localized to both stromal and tumor epithelial cells (Okada et al, 1995;Polette et al, 1996Polette et al, , 1997Ueno et al, 1997;Bisson et al, 2003;Rosenthal et al, 2004;Szabova et al, 2005). To analyse the role of MT1-MMP in an in vivo tumor model directly, we crossed mice deficient for MT1-MMP (Holmbeck et al, 1999) to a mouse strain carrying the polyoma virus middle T-antigen (PyMT) under the control of the mouse mammary tumor virus (MMTV) promoter (Guy et al, 1992).…”
Section: Introductionmentioning
confidence: 99%